2007
DOI: 10.1007/s11023-007-9070-6
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Generation of Cognitive Theories using Genetic Programming

Abstract: Abstract.Cognitive neuroscience is the branch of neuroscience that studies the neural mechanisms underpinning cognition and develops theories explaining them. Within cognitive neuroscience, computational neuroscience focuses on modeling behavior, using theories expressed as computer programs. Up to now, computational theories have been formulated by neuroscientists. In this paper, we present a new approach to theory development in neuroscience: the automatic generation and testing of cognitive theories using g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…An extension of this idea is to use the canonical results as a target for the automatic generation of theories. In unrelated work, Frias-Martinez and Gobet [8] have shown how theories may be generated automatically using genetic programming. The quality of the theories is judged based on their fitness to a standard set of experimental data -this standard data, in our terminology, would form the canonical results of the resultant theories.…”
Section: Discussionmentioning
confidence: 99%
“…An extension of this idea is to use the canonical results as a target for the automatic generation of theories. In unrelated work, Frias-Martinez and Gobet [8] have shown how theories may be generated automatically using genetic programming. The quality of the theories is judged based on their fitness to a standard set of experimental data -this standard data, in our terminology, would form the canonical results of the resultant theories.…”
Section: Discussionmentioning
confidence: 99%
“…learning algorithms) of the models to be evolved. Frias-Martinez and Gobet (2007), using genetic programming, have shown that this is possible with a simple task. Third, our method focuses on parameter optimisation, but does not address issues such as theory parsimony when comparing models.…”
Section: Discussionmentioning
confidence: 99%
“…At the very least, it requires acquiring skills in computer science and programming in addition to skills specific to a particular domain, such as psychology. In addition, the generation of scientific models can be described as a heuristic search in the combinatorial space of all the possible candidate models that explain a specific phenomenon (Frias-Martinez & Gobet, 2007; Simon, 1977). Given the infinite size of such spaces, searching them can be difficult indeed, both theoretically and computationally, and human scientists can explore only a limited portion of those spaces.…”
Section: Value-based Decision-makingmentioning
confidence: 99%